PENGARUH PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA PT KERETA API INDONESIA DI JAKARTA PUSAT - Aprilia Edy Setiowati, My; Sirajuddin (Journal of Research and Publication Innovation, 2023)
The aim of this research is to determine the effect of training and work discipline simultaneously on the performance of employees of PT Kereta Api Indonesia in Central Jakarta. The method used in this research is a quantitative method. The population in this study were all employees of 87 respondents. The sampling technique in this study uses a saturated sampling technique or where all members of the population are sampled. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis t test and hypothesis f test. The results of this research are that training has a significant effect on employee performance with the regression equation Y = 12.752 + 0.793 ) has a very strong level of influence on the employee performance variable (Y) with a coefficient of determination of 87.6% and the hypothesis test obtained t count > t table or (6.065 > 1.988). Work discipline has a significant effect on employee performance with the regression equation Y = 23.646 + 0.892 ) has a strong level of influence on the employee performance variable (Y) with a coefficient of determination of 28% and hypothesis testing obtained t count > t table or (3.354 > 1.988). Training and work discipline have a significant effect on employee performance with the regression equation Y = 8.795 + 0.758 X1 + 0.136 X2. The correlation coefficient value obtained was 0.939, meaning that the training variable (X1) with the work discipline variable (X2) had a very strong level of influence on the employee performance variable (Y) with a simultaneous coefficient of determination or influence of 88.1% while the remainder was 11.9 % influenced by other factors. Hypothesis testing obtained a calculated f value > f table or (312.115 > 2.71), this was also strengthened by a significance probability of 0.001 < 0.05. Thus H0 is rejected and H3 is accepted. This means that there is a significant influence between training and work disciplinesimultaneously on the performance of PT Kereta Api Indonesia employees in Central Jakarta.